Iron deficiency in long standing type 1 diabetes mellitus and its association with depression and impaired quality of life. (May 2019) - Bergis, Dominik; Tessmer, Lea; Badenhoop, Klaus
Highlights: This study indicates a relation of ID, depression and impaired QoL in type 1 diabetes. Depression rate was high and and QoL was impaired despite good glycemic control. Sufficient serum ferritin and iron levels were associated with a better QoL. Serum ferritin levels predicted a better well-being measured by WHO5-Scale. Abstract: Aims: Iron deficiency (ID) is the most frequent malnutrition worldwide and often associated with reduced quality of life (QoL) and depression. We aimed to investigate the iron status in middle-aged type 1 diabetes in relation to depression and QoL. Methods: 109 people with type 1 diabetes (54.1% male, mean age 56.2 years) were enrolled in a cross-sectional study at the diabetes clinic of the Goethe University Hospital. Iron, haemoglobin and ferritin levels were measured. Treatment satisfaction, QoL and depression were assessed using standardized questionnaires (Disease Specific Quality of Life scale, CES-D (Center for Epidemiological Studies Depression Scale) and WHO-5 well-being index. Results: Decreased serum iron (<60 µg/dl) and ferritin levels (<50 pg/nl) were observed in 18 (16.8%) and 28 (26.7%) patients, respectively. Anemia was present in 20 patients (18.34%). A high rate of depression was observed: 42.2% (WHO-5) and 40.7% (CES-D). The personal goals and current diabetes therapy satisfaction score (PWTSS) was significantly better in patients with sufficient iron status (ferritin level > 50 pg/ml, p = 0.018). Multiple regression analysis revealed iron status (p = 0.03) to be an independent predictor for better PWTSS. Insufficient iron status correlated significantly with depression as measured by WHO-5 (p = 0.044) and CES-D (p = 0.029). Conclusions: Type 1 diabetes patients in the current study were frequently depressive and reported an impaired QoL that associated with iron insufficiency. If confirmed a better awareness is needed for depression and ID in long standing disease.